The traditional use of medicinal plants to treat erectile dysfunction and the isolation of their bioactive compounds - Meyer, J.J.M. (Jacobus Johannes Marion) (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2002.